The skeptic, the content externalist, and the theist - Howell, Robert (International journal for philosophy of religion, 2011)
Some philosophers argue that content externalism can provide the foundations of an argument against the traditional epistemological skeptic. I maintain that if such an argument is available, it seems there is also an a priori argument against the possibility of a creationist god. My suspicion is that such a strong consequence is not desirable for the content-externalists, and that the availability of this argument therefore casts doubt on the anti-skeptical position. I argue that all content externalists should be troubled by this result, since even those philosophers who do not endorse the anti-skeptical strategy must either reject the possibility of a creationist god or admit that their thesis does not hold a priori for minds in general.